2010
DOI: 10.1038/nn.2555
|View full text |Cite
|
Sign up to set email alerts
|

Lack of cadherins Celsr2 and Celsr3 impairs ependymal ciliogenesis, leading to fatal hydrocephalus

Abstract: Cilia are organelles that protrude from the apical surface of most eukaryotic cells. According to their structure and motility, they are classified into three groups 1 . Primary monocilia, present in most cells, lack a central pair of microtubules (9+0 structure), and play several roles in mechanosensation and cell signaling. Nodal cilia have a 9+0 structure but, unlike primary cilia, they move and generate an asymmetric distribution of morphogenetic cues in the node, thereby contributing to laterality 2 . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
337
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 309 publications
(367 citation statements)
references
References 50 publications
21
337
1
4
Order By: Relevance
“…Genetic deficiency of genes such as Mdnah5 (Ibanez-Tallon et al, 2004), Tg737 (Banizs et al, 2005, Hy3 (Davy and Robinson, 2003), Celsr2/3 (Tissir et al, 2010), Foxj1 (Jacquet et al, 2009), Six3 (Lavado and Oliver, 2011), c-Myb (Malaterre et al, 2008, and Snx27 results in impaired ciliogenesis and hydrocephalus. Interestingly, we observed that Snx27 deletion results in deficiencies in proper ependymal cell differentiation to ependymal cell types with a compensatory increase in differentiation to nonciliated cells (Páez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic deficiency of genes such as Mdnah5 (Ibanez-Tallon et al, 2004), Tg737 (Banizs et al, 2005, Hy3 (Davy and Robinson, 2003), Celsr2/3 (Tissir et al, 2010), Foxj1 (Jacquet et al, 2009), Six3 (Lavado and Oliver, 2011), c-Myb (Malaterre et al, 2008, and Snx27 results in impaired ciliogenesis and hydrocephalus. Interestingly, we observed that Snx27 deletion results in deficiencies in proper ependymal cell differentiation to ependymal cell types with a compensatory increase in differentiation to nonciliated cells (Páez et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Notch signaling blocks Snx27 deletionassociated ependymal cell loss and partially rescues hydrocephalus in Snx27 ؊ / ؊ mice It has been reported that overexpression of the NICD leads to a reduced number of ciliated cells and, conversely, that repression of Notch signaling results in an increased number of precursor cells adopting a multiciliated cell fate (Deblandre et al, 1999;Tsao et al, 2009;Marcet et al, 2011). Although our previous findings indicate that SNX27 deficiency upregulates ␥-secretase cleavage of Notch and generation of NICD (Wang et al, 2014b), it was unclear how SNX27-mediated ␥-secretase suppression could influence pathophysiological brain development.…”
Section: Snx27 Deletion Leads To the Disorganization Of Ependymal Adhmentioning
confidence: 99%
“…Celsr1 is expressed in FBM neuron precursors and the floor plate, but not in FBM neurons, which helps to specify the direction of FBM neuron migration in a noncell autonomous manner. In Celsr2-/-mutants, the initiation of FBM neuron migration is normal but these neurons This cooperative action is also found in the planar organization of ependymal cilia regulated by Celsr2 and Celsr3 [50] . Celsr2-deficient mice show defective cerebrospinal fluid dynamics and hydrocephalus, and the polarity of ependymal cilia is disrupted.…”
Section: Cooperative Actions Of Celsr1-3 In Neural Developmentmentioning
confidence: 90%
“…Single-Celsr knockout mice show different phenotypes, such as the failure of axonal projections in Celsr3-/- [38] , abnormal organization of ependymal cilia in Celsr2-/- [50] , and improper neuronal migration in Celsr1-/- [49] . However, …”
Section: Summary and Prospectsmentioning
confidence: 99%
“…23 Normal production and circulation of the CSF are known to be crucial for proper brain development. 24,25 For example, Wnt4 and Wnt modulator Tgm2 are regulated by Otx2, a master regulator of choroid plexus development which produces CSF. 24 We showed recently that Ulk4 is essential for ciliogenesis and CSF flow.…”
mentioning
confidence: 99%